2021
DOI: 10.1002/marc.202100589
|View full text |Cite
|
Sign up to set email alerts
|

Low Fouling Polysulfobetaines with Variable Hydrophobic Content

Abstract: Amphiphilic polymer coatings combining hydrophilic elements, in particular zwitterionic groups, and hydrophobic elements comprise a promising strategy to decrease biofouling. However, the influence of the content of the hydrophobic component in zwitterionic coatings on the interfacial molecular reorganization dynamics and the anti-fouling performance is not well understood. Therefore, coatings of amphiphilic copolymers of sulfobetaine methacrylate 3-[N-2'-(methacryloyloxy)ethyl-N,N-dimethyl]-ammonio propane-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 77 publications
(111 reference statements)
1
18
0
Order By: Relevance
“…As these surface‐attached polymer networks have a low cross‐linking density, and hence significant structural flexibility, the contact angle differences between the determined data set and the literature data could be due to molecular rearrangements at the interface, particularly of the hydrophobic moieties of the polymers, that occur to lower the overall surface energy of the system when stored in air. Interestingly, for the series E 1 to E 3 , one previous study also found that E 2 had the highest static contact angle of the three, [ 35 ] although it was not the polymer with the highest fraction of hydrophobic butyl repeat units. While the reasons for these results are not yet understood (and indeed are not the main focus of this work), this qualitative agreement in the data conforms to the validity and consistency of the here presented measurements.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As these surface‐attached polymer networks have a low cross‐linking density, and hence significant structural flexibility, the contact angle differences between the determined data set and the literature data could be due to molecular rearrangements at the interface, particularly of the hydrophobic moieties of the polymers, that occur to lower the overall surface energy of the system when stored in air. Interestingly, for the series E 1 to E 3 , one previous study also found that E 2 had the highest static contact angle of the three, [ 35 ] although it was not the polymer with the highest fraction of hydrophobic butyl repeat units. While the reasons for these results are not yet understood (and indeed are not the main focus of this work), this qualitative agreement in the data conforms to the validity and consistency of the here presented measurements.…”
Section: Resultsmentioning
confidence: 96%
“…[34], and of E 1 to E 3 in ref. [35]. Polymer C was prepared analogously to D 1 , and E 4 analogously to E 1 , employing the respective zwitterionic methacrylates which were made as described before.…”
Section: Methodsmentioning
confidence: 99%
“…and their zoospores and Navicula sp.) and measured cell attachment, settlement, and viability on the studied surface (Leonardi & Ober, 2019) For example, amphiphilic surface‐active PDMAEMA brushes or SPE/BMA copolymers displayed anti‐biofouling properties against algae and zoospore settlement as well as growth‐inhibitory activity (Schardt et al, 2021; Yandi et al, 2017). The recent developments in this field focusing on both advantages and drawbacks of these coatings have been reviewed intensively elsewhere, and we encourage the interested reader to explore these references (Galli & Martinelli, 2017; Leonardi & Ober, 2019; Qiu et al, 2022).…”
Section: New Targetsmentioning
confidence: 99%
“…In this regard, passive antifouling coatings, which prevent the attachment of molecules and microorganisms, are an important research area . Hydrophilic polymers grafted onto surfaces create a strong hydration layer, and the attachment of foulants would compress this polymer brush and lead to a reduction of hydration, hence both processes are thermodynamically unfavorable. Poly­(ethylene glycol) (PEG) brushes are frequently used for this purpose but also other polymers such as poly­(2-hydroxypropylmethacrylamide), , polysarcosine, or zwitterionic polymers are reported. Another promising alternative to PEG in antifouling applications is poly­(2-oxazoline)­s (POx). Depending on the used monomer, POx can be biocompatible/nontoxic and show stealth behavior similar to PEG. …”
Section: Introductionmentioning
confidence: 99%